UNDERSTANDING LEARNING STYLES IS CRUCIAL FOR EDUCATORS (Ta'limning zamonaviy transformatsiyasi, 2025)
Abstract:This study explores the relationship between secondary school students' preferred learning styles and demographic factors such as gender, place of residence, religion, and parents' education level. The research was conducted with a sample of 300 secondary school students from Aligarh District, using the Learning Style Inventory developed by Jeffrey Barsch. Since the data was nominal, the Chi-Square test was employed for analysis. The study's findings revealed that the most preferred learning style among the students was visual, followed by auditory, kinesthetic, and tactile styles. Additionally, the study showed no significant impact of factors like gender, place of residence, religion, or father’s education level on students' learning style preferences. However, the mother’s education level was found to have a significant influence on these preferences.